The Shark Jaw and the Elevator: Arguing the Case for the Necessity, Harmlessness and Fairness of the Norwegian Pension Reform. (15th March 2015) - Ervik, Rune; Lindén, Tord Skogedal
Abstract : Based on the retrenchment literature, Norway is an unlikely candidate for comprehensive pension reform because of its unique economic situation, with a steadily growing petroleum fund and substantial tax revenues flowing into the public coffers. Thus, politicians should encounter difficulty convincing the electorate and strong interest groups of the need for reform. Nevertheless, reform did occur in Norway, and reform justifications faced surprisingly brief and light opposition. This article investigates the policy discourses applied and argues that two images of justification in the Norwegian pension reform process partially explain how resistance to the reform was overcome. The first image is a type of crisis scenario that is neatly cached in the 'shark jaw' image. The shark jaw can be visualised in a graphic illustration in which projected future petroleum revenues and pension expenses are displayed simultaneously. The lines for the two indicators extend in opposite directions, forming an image resembling a jaw. The second image frames the actual reform as an improvement; this view illustrates how the reform allows one to enter an 'elevator' that moves one upwards, presenting a stark contrast to the substance of retrenchment. The article is informed by Schmidt's discursive‐institutionalism perspective and her distinction between coordinative and communicative discourses. Empirically, the article relies on a comprehensive collection of materials, including document analysis, parliamentary debates, interviews, media searches and opinion surveys.